Airport carbon footprint: a case study for Lanseria International Airport - Chimhau, Tania (My University, 2022)
Climate change is a worrying occurrence, and the rate at which it is changing has exacerbated land degradation. Due to a shift in the global climate zones, rainfall has increased, inevitably leading to severe floods, rising sea levels, hurricanes, excessive winds, typhoons, and more. Climate change affects human health and impacts the availability of basic human necessities such as food security, energy, and freshwater. This mainly affects poor developing countries’ environmental health, economic and social systems. Increases in the concentration of greenhouse gases and global temperature have raised concerns globally and locally. According to the Intergovernmental Panel on Climate Change, the global transport sector accounts for 21% of the worldwide greenhouse gas (GHG) emissions, while aviation accounts for 2.5%. However, aviation activities are increasingly economically important, despite being one of the fastest-growing greenhouse gas emitters globally. Airport environmental protection has become crucial to the global air transport industry, becoming more environmentally aware and increasing their efforts to reduce their environmental impact. This dissertation explores the carbon footprint of the activities taking place at Lanseria International Airport (LIA), situated in the Gauteng province in South Africa within the Johannesburg Metropolitan area. The GHG emissions were quantified using an Airport GHG emissions calculation tool. The ACERT airport carbon footprint tool considers all emission sources in and around airports. To comply with the proposed objectives, monthly raw data and source documents for all emission activities at LIA were provided by the environmental management team at the airport. The airport was responsible for 113 069, 112 575, and 83 503 tCO2e emitted during 2018, 2019 and 2020, respectively. Scope 3 GHG emissions dominated and accounted for a significant portion of the total carbon footprint. This scope category is out of the airport’s control. Where the airport has control, the emissions are dominated by electrical consumption, which on average accounts for 95% of the Scope 1 and 2 GHG emissions. In the 2019 financial year, LIA generally performed better than in 2018, as the airport implemented multiple projects, including the retrofitting project, to minimize the energy consumption at the airport. In 2020, the airport had a relatively low carbon footprint, as its activities and operation were affected by the COVID-19 pandemic. The decline in GHG emissions is beneficial as fewer GHG emissions are an advantage in the fight against global climate change. However, the decline in the transportation of freight and passengers renders this a period of crisis concerning business. The carbon footprint case study for Lanseria International airport demonstrates that the airport operates sustainably. However, to effectively reduce the carbon footprint, the airport is advised to minimise emissions under their direct control. Scope 2 emissions dominate the direct GHG emissions. Therefore, it is recommended that the airport introduce renewable alternative energy sources to mitigate the grid's electricity usage.
A dissertation submitted in fulfilment of the requirements for the Degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2022